Improving Student Learning Outcomes Using the Index Card Match Method in Asmaul Husna Materials in Elementary School - Eti Eta Susana; Musthafa Kamal; Achmad Zuhri (FITK UIN Walisongo Semarang, 2025)
This Classroom Action Research (PTK) aims to improve the learning outcomes of grade II students of SD Negeri Wringinjajar 1 in the subject of Islamic Religious Education in Asmaul Husna material through the application of the Problem Based Learning (PBL) model and the Index Card Match method. The research was carried out in two cycles with the research subject of grade II A students for the 2024/2025 academic year. Based on the results of the study, there was a significant increase in the aspects of readiness, attention, activeness, and completeness of students' learning. The average value of learning outcomes increased from pre-cycle by 53.33% to 66.67% in cycle I and 76.67% in cycle II. In addition, the use of Asmaul Husna card media also supports student understanding, where the average score increased from 63 (pre-cycle) to 72.5% in cycle I and 79.67% in cycle II, accompanied by an increase in learning completeness from 46.67% to 73.33%, then 93.33%. The conclusion of this study shows that the combination of the PBL model and the Index Card Match method is effective in improving student learning outcomes, both qualitatively and quantitatively, so that it is suitable for application in PAIBP learning, especially in Asmaul Husna material.